2012
DOI: 10.1308/003588412x13171221501942
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric injuries due to home treadmill use: an emerging problem

Abstract: Treadmills can pose a significant danger to children. These injuries are preventable. Regulatory authorities, manufacturers and parents should take steps to prevent this emerging health problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Concern regarding injury to growth plates during resistance training appears to be unfounded, with no evidence to date that weight lifting negatively affects growth or maturation [11,13]. A limited number of case reports in which authors suggested a risk of epiphyseal injuries of the limbs or injuries to the spine likely were related to use of improper techniques or inadequate supervision [14‐17]. Compromised technique that results from the desire to lift heavier weights can lead to injury, as can unsupervised lifting.…”
Section: Resistance Trainingmentioning
confidence: 99%
“…Concern regarding injury to growth plates during resistance training appears to be unfounded, with no evidence to date that weight lifting negatively affects growth or maturation [11,13]. A limited number of case reports in which authors suggested a risk of epiphyseal injuries of the limbs or injuries to the spine likely were related to use of improper techniques or inadequate supervision [14‐17]. Compromised technique that results from the desire to lift heavier weights can lead to injury, as can unsupervised lifting.…”
Section: Resistance Trainingmentioning
confidence: 99%
“…Therefore, risk factors are not limited to the machine itself, but also the present of parents and children's peer friends. Parents should be cautious with their surroundings and avoid wearing headsets ( 18 ) or other devices that interfere with perception when using the treadmill, and children should be banned from using treadmills alone or with their friends.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the pattern of injuries observed in this study may be specific to the USA. However, studies in other countries have similarly described paediatric injuries from treadmills and exercise bicycles 6 8 9 17. Preventing injuries from mechanical home exercise equipment is relevant to countries where exercising at home may also be common.…”
Section: Discussionmentioning
confidence: 99%